Dry eye and Demodex - Bruenech, Jan Richard; Haugen, Inga-Britt Kjellevold (Scandinavian Journal of Optometry and Visual Science, 2014)
Abstract Dry eye syndrome (DES) is a common condition causing dry eye sensation and ocular inflammation. The etiology is not fully explored, but clinical trials have demonstrated that the secretory functions of the eyelids can be compromised by microorganisms. Demodex are parasites which also can infest the follicles and glands of the lids, but their adverse effect is not equally documented. The purpose of this study is to examine these parasites and their potential implication in the development of DES and other ocular conditions. Transverse sections of the eyelids from 4 donors were processed through standard histochemical techniques, while 24 eyelashes were methodically extracted from the eyelids of a selected mature subject identified with DES. The sections and the eyelashes were analysed through light microscopy. Thirty-eight parasites were identified. They had a length of 300-555µm and diameter of 30-75µm. Histological examination of the donor eyelids suggested that follicles accommodate considerably more secretory substance (in which most parasites are embedded) than what is revealed through conventional methods of lash extraction. It is therefore legitimate to assume that a population of Demodex is arguably larger than indicated by most clinical methods. Furthermore, the tubular system inside the meibomian glands was found to have diameters that corresponded with the diameters of the parasites, which indicates tha the parasites are physically capable of blocking the secretory passageways. Finally, the parasites have eight segmented, claw-shaped legs with large ranges of motion. The mechanical and immunological provocation they inflict on houst tissues is arguably sufficient to cause inflammation. This paper promotes the view that when a population of Demodex reaches a critical level it has the capacity to cause secretory dysfunctions in the eyelids and may hence be implicated in the etiology of DES and other ocular inflammatory conditions. Sammendrag «Dry eye syndrome» (DES) er en hyppig tilstand som gir tørrhetsfølelse og okulær inflammasjon. Etiologien er ikke fullstendig kartlagt, men kliniske studier har vist at mikroorganismer kan bidra til å skape dysfunksjoner i øyelokkets sekretoriske system. Demodex er parasitter som også kan infisere hårfollikler og kjertler i øyelokket, men den helsemessige betydningen av disse organismene er mindre dokumentert. Hensikten med dette studiet er å analysere parasittenes egenskaper for å se om de kan være involvert i etiologien til DES og andre okulære lidelser. Transversale snitt av øyelokket til 4 donorer ble preparert med standard histokjemiske metoder, mens 24 cilier ble metodisk epilert fra øyelokket på en utvalgt voksen forsøksperson identifisert med DES. Snittene og ciliene ble analysert med lysmikroskop. Totalt 38 parasitter ble identifisert. De hadde en lengde på 300-555µm og diameter på 30-75µm. Histologiske analyser av donorvevet indikerte at folliklene inneholder vesentlig mer sekret (hvor flest parasitter oppholder seg) enn det som fremkommer ved bruk av tradisjonelle epileringsmetoder. Det er derfor naturlig å anta at populasjonen av Demodex trolig er større enn det som påvises ved hjelp av de fleste kliniske metoder. Analyser av de meibomske kjertlene viste at diameteren på deres tubulære kanaler hadde tilnærmet lik diameter som parasittene, hvilket indikerer at parasittene er i stand til å fysisk blokkere kjertlenes interne transportsystem. Parasittene har åtte leddede klo-formede ben med store bevegelsesmuligheter. Deres mekaniske og immunologiske påvirkning på vertsvevet vil trolig være tilstrekkelig til å trigge inflammatoriske responser. Artikkelen konkluderer med at når størrelsen på en populasjon med Demodex når et kritisk nivå vil den kunne skape sekretoriske dysfunksjoner i øyelokket og således forårsake tilstander som DES og et bredt spekter av andre okulære tilstander.